Herausforderungen und Zukunftsperspektiven für den Sachunterricht - Schmeinck, Daniela; Michalik, Kerstin; Goll, Thomas (Probleme und Perspektiven des Sachunterrichts, 2023)
Our world today is characterized by accelerated social, technological, and digital change, as well as a plurality of lifestyles. These developments offer new opportunities for teaching and learning in science education, but at the same time they also pose new challenges for science education. How do educational and learning processes have to be designed with regard to a democratic, pluralistic and digital society and an unpredictable future in order to prepare students to deal with diversity, uncertainty and complexity in a critical and constructive way? What innovations in science education and its didactics are necessary to achieve this? This volume examines the challenges and future perspectives for science education in relation to digitization and digitality, sustainability and education for sustainable development, democracy education and political education, uncertainty, non-knowledge and questioning of previous certainties, as well as under cross-perspective and perspective-related issues.